EFEKTIVITAS DINAS TENAGA KERJA KOTA SAMARINDA SEBAGAI MEDIATOR DALAM PENYELESAIAN PERSELISIHAN HUBUNGAN - Fidelius Pakalla (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
AbstractThe importance of mediation as an alternative dispute resolution outside the court, as well as the ancestral culture of the Indonesian people who always prioritize deliberation at each problem solving for consensus. The research method used in writing this thesis is a normative juridical method and empirical juridical. The writing of this thesis refers to the theory of organizational effectiveness and based on the mediation mechanism regulated in Law No. 2 of 2004 concerning Industrial Relations Dispute Resolution and Minister of Manpower and Transmigration Regulation Number 17 of 2014 concerning Appointment and Dismissal of Industrial Relations Mediators and Mediation Work Procedures. The results of the research and discussion in this paper indicate that the Samarinda City Manpower Office as a mediator has been quite effective in resolving industrial relations disputes. This can be seen from the data in the form of a table of results on the industrial relations dispute resolution especially in 2017 and 2018 layoff disputes where 72 cases can be resolved peacefully and reach agreement through collective agreements, while the cases completed with written recommendations are 39 cases . This opinion was also strengthened through the results of interviews with writers and several mediators who had sufficient experiences in carrying out their duties based on effective labor law and pre-supporting facilities. The obstacle for the Samarinda City Manpower Service mediator in resolving industrial relations disputes is the lack of clarity of information from inter-personal or one of the parties to the dispute, the difficulty of presenting inter-personal or one party to mediation, especially entrepreneurs who do not have a representative office in Samarinda City, completeness of data from the parties, indifferent attitude of some employers to labor legislation, and the involvement of other interested parties.